1984
DOI: 10.1073/pnas.81.21.6851
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric human antibody molecules: mouse antigen-binding domains with human constant region domains.

Abstract: We have created mouse-human antibody molecules of defined antigen-binding specificity by taking the variable region genes of a mouse antibody-producing myeloma cell line with known antigen-binding specificity and joining them to human immunoglobulin constant region genes using recombinant DNA techniques. Chimeric genes were constructed that utilized the rearranged and expressed antigen-binding variable region exons from the myeloma cell line S107, which produces an IgA (K) anti-phosphocholine antibody. The hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
313
0
21

Year Published

1987
1987
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 891 publications
(335 citation statements)
references
References 17 publications
1
313
0
21
Order By: Relevance
“…Plasmids Plasmid g1NANP carries a chimeric H chain gene in which the productively rearranged murine V H 62 region gene 26 is joined to the human g1 C region gene of the pNeog1 vector. 68 The V region gene was modified in the third CDR3 by introduction of three NANP repeats. 69 The promoter and enhancer elements in this plasmid are those constitutively existing in Ig H chain genes, and were described previously.…”
Section: Transgenesis Of Human B Lymphocytes G Filaci Et Almentioning
confidence: 99%
“…Plasmids Plasmid g1NANP carries a chimeric H chain gene in which the productively rearranged murine V H 62 region gene 26 is joined to the human g1 C region gene of the pNeog1 vector. 68 The V region gene was modified in the third CDR3 by introduction of three NANP repeats. 69 The promoter and enhancer elements in this plasmid are those constitutively existing in Ig H chain genes, and were described previously.…”
Section: Transgenesis Of Human B Lymphocytes G Filaci Et Almentioning
confidence: 99%
“…Variable (V) regions bind antigens (Ag) and constant (C) parts bear effector functions Correspondence address: Y. Kurosawa, Institute for Comprehensive Medical Science, Fujita-Gakuen Health University, Toyoake, Aichi 470-l 1, Japan Abbreviations: Ab, antibody; Ag, antigen; C, constant; D, diversity; ELISA, enzyme-linked immunosorbent assay; H, heavy; Ig, immunoglobulin; J, joining; L, light; PAB, pazobenzenarsonate; PAGE, polyacrylamide gel electrophoresis; PBS, phosphate-buffered saline; PC, phosphorylcholine; V, variable such as binding and activation of complements, stimulation of phagocytosis by macrophages, and triggering of granule release by mast cells. Utilizing the dual characters in the structure of Ab, two research groups [3,4] succeeded in constructing chimeric molecules consisting of mouse-derived V regions and human-derived C regions. These chimeric Ab retained specificity for the haptens phosphorylcholine (PC) [3] and trinitrophenyl [4].…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing the dual characters in the structure of Ab, two research groups [3,4] succeeded in constructing chimeric molecules consisting of mouse-derived V regions and human-derived C regions. These chimeric Ab retained specificity for the haptens phosphorylcholine (PC) [3] and trinitrophenyl [4]. Since these studies several groups have reported production of similar chimeric Ab showing antitumor activities [5-l 11.…”
Section: Introductionmentioning
confidence: 99%
“…9 CD80 et CD86, membres de la famille des molĂ©cules B27, impliquĂ©es dans la coactivation lymphocytaire. De plus en plus de nouveaux formats issus de l'ingĂ©nie-rie molĂ©culaire (protĂ©ines-Fc ou Fab ; CDR, domaines charniĂšres et constants, glycanes optimisĂ©s) ou chimique (conjuguĂ©s) sont dĂ©veloppĂ©s avec succĂšs dans leurs applications pharmaceutiques et cliniques, ce qui dĂ©montre la versatilitĂ© structurale des IgG et de leurs sous-domaines.…”
unclassified